(3GdaYGdjGJ hYhGed GdLOGQIs - (3TQja(B, (3eMeO eGgQs ((3GdEScfOQjI(B:s (3OGQ GdLGeYI(B,s, 2006)
(3YdGbI GdJNWjW hGdSjGSI heLJeY Gdfbd HGddhLSJjGJ(B-(3JNWjW Gdfbd(B-(3OjehLQGajI GdTYhH GdYQHjI hJCKjQgG Ydi JNWjW YedjGJ Gdfbd(B-(3GdJNWjW GdESJQGJjLj(B-(3JNWjW Gdfbd eJYOO GdhSGFW(B-(3JNWjW Yed GdehGfF GSJQGJjLjI JNWjW Gdfbd Hjf GdOhd GdYQHjI SjGSGJ Gdfbd GdOhdj(B-(3EYGOI HfGA hgfOSI hGSJQGJjLjGJ Gdfbd(B-(3eLJeY Gdfbds
(3bGFeI GdeNJUQGJ HGddZI GdCfLdjRjIs
Keywords: (3GdJNWjWs; (3GdJNWjW GdESJQGJjLjs; (3Gdfbds; (3SjGSI Gdfbds; (3Yed GdehGfFs; (3eLJeY Gdfbds